Google hacking for penetration testers. - Long, Johnny (Syngress Pub., 2008)
A self-respecting Google hacker spends hours trolling the Internet for juicy stuff. Firing off search after search, they thrive on the thrill of finding clean, mean, streamlined queries and get a real rush from sharing those queries and trading screenshots of their findings. I know because Ive seen it with my own eyes. As the founder of the Google Hacking Database (GHDB) and the Search engine hacking forums at http://johnny.ihackstuff.com, I am constantly amazed at what the Google hacking community comes up with. It turns out the rumors are truecreative Google searches can reveal medical, financial, proprietary and even classified information. Despite government edicts, regulation and protection acts like HIPPA and the constant barking of security watchdogs, this problem still persists. Stuff still makes it out onto the web, and Google hackers snatch it right up. Protect yourself from Google hackers with this new volume of information. Johnny Long Learn Google Searching Basics Explore Googles Web-based Interface, build Google queries, and work with Google URLs. Use Advanced Operators to Perform Advanced Queries Combine advanced operators and learn about colliding operators and bad search-fu. Learn the Ways of the Google Hacker See how to use caches for anonymity and review directory listings and traversal techniques. Review Document Grinding and Database Digging See the ways to use Google to locate documents and then search within the documents to locate information. Understand Googles Part in an Information Collection Framework Learn the principles of automating searches and the applications of data mining. Locate Exploits and Finding Targets Locate exploit code and then vulnerable targets. See Ten Simple Security Searches Learn a few searches that give good results just about every time and are good for a security assessment. Track Down Web Servers Locate and profile web servers, login portals, network hardware and utilities. See How Bad Guys Troll for Data Find ways to search for usernames, passwords, credit card numbers, social security numbers, and other juicy information. Hack Google Services Learn more about the AJAX Search API, Calendar, Blogger, Blog Search, and more.
Keywords: Google.; Google; Web search engines.; Computer security.; Internet programming.; Internet -- Security measures.; Computer networks -- Security measures.; Moteurs de recherche sur Internet.; Sécurité informatique.; Programmation Internet.; Internet -- Sécurité -- Mesures.; Réseaux d'ordinateurs -- Sécurité -- Mesures.; COMPUTERS -- Online Services.; COMPUTERS -- System Administration -- Storage & Retrieval.; Computer networks -- Security measures; Computer security; Internet programming; Internet -- Security measures; Web search engines